TORAKOCHIRURGIAOccurrence of Candida fungi in bronchoalveolar lavage in patients with lung neoplastic tumour - Szymankiewicz, Maria; Dancewicz, Maciej; Bella, Mariusz; Kowalewski, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Background: Respiratory infections are very frequent in lung cancer patients. Their diagnosis, especially diagnosis of pulmonary candidiasis, is difficult because of the lack of specific clinical manifestations. Aim: The objective of this study was to assess the occurrence of Candida fungi in bronchoalveolar lavage (BAL) in patients with neoplastic tumour of the lung. We also tried to estimate the significance of the isolation of Candida spp. in quantitative cultures of BAL. Material and Methods: 44 patients with lung neoplastic tumour were included in this study. Materials for microbiological examinations were taken during bronchoscopy and sent to the Microbiology Department for fungal isolation and identification. Quantitative cultures of BAL fluid were performed by using Sabouraud agar (bioMérieux) and calibrated loops (1: 100 and 1: 1000). Materials were also cultured onto Sabouraud gentamicin and chloramphenicol agar (bioMérieux). The plates were incubated for 5 days at 30°C. Yeast-like fungi were identified by standard laboratory methods. Results are expressed as colony forming units per millilitre (cfu/ml). Results: Growth of Candida spp. in any count was seen in 15 of 44 examined patients (34.09%): one isolate in 14 patients and two isolates in 1 patient. The most frequently identified species was C. albicans. The isolation of Candida spp. in quantity ł104 cfu/ml was observed only in 3 patients (6.82%). Regardless of result of quantitative cultures none of the patients demonstrated any clinical manifestations of respiratory infection. Conclusions: The isolation of Candida spp., especially C. albicans, from BAL was frequent in patients with lung cancer but the presence of Candida spp. in quantity ł104 cfu/ml was rare. In all examined patients the isolation of Candida fungi indicated colonization of the bronchial tree.